Time to Surgery and Patient Mortality in Geriatric Acetabular Fractures. Issue 6 (June 2020) - Glogovac, Georgina; Le, Theodore Toan; Archdeacon, Michael T.
Abstract : Objectives: To determine whether surgical intervention within 48 hours of injury results in decreased mortality in geriatric patients who have sustained acetabular fractures. Design: Retrospective case series. Setting: University Level 1 Trauma Center. Patients/Participants: One hundred eighty-three patients 65 years of age and older who were operatively treated for acetabular fractures between 2002 and 2017. The average age was 76 years. Intervention: Operative fixation of acetabular fracture. Main Outcome Measurements: Chi square tests were used to compare 30-day, 6-month, and 1-year mortality after operative intervention between patients treated within 48 hours and after 48 hours. A Cox proportional hazard model was used to determine predictors of mortality. Results: The overall 1-year morality was 15%. When patients were grouped by time to surgery (fracture fixation within 48 hours or after 48 hours), there were no statistically significant differences in 30-day, 6-month, or 1-year mortality between groups. In addition, there were no statistically significant differences in age, sex, mechanism of injury, fracture pattern, Charlson comorbidity index, length of hospital stay, presence of deep vein thrombosis, or quality of reduction. In the final multivariate Cox regression model of survival, increasing age was associated with a significantly increased hazard of death with a hazard ratio (HR) of 1.09 (95% confidence interval, 1.05–1.13) per year of age ( P < 0.001). Patient sex, mechanism of injury, fracture pattern, estimated blood loss, and Charlson comorbidity index were not significant predictors of mortality. Conclusion: In contrast to the clear mortality benefits of early surgical intervention in geriatric patients with proximal femur fractures, the results of our study suggest that surgical intervention after 48 hours of injury is not associated with increased mortality rates in geriatric patients with acetabular fractures. Increased mortality was independently associated with advancing age. Sex, mechanism of injury, and facture pattern were not associated with mortality. Time to surgery in geriatric patients with acetabular fractures should be determined on an individual basis. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.